A Case Study on the Use of Creative Drama in Art Education Courses - Esra ÇİFÇİ; Aynur KILIÇ; Betül YAYLI; Ayşegül OĞUZ NAMDAR (IDA: International Design and Art Journal, 2020)
This study was carried out in order to expose the opinions of the teachers teaching art education courses about the use of creative drama in art course. According to the nature of the study among qualitative research designs the case study design was used. This research using the case study was conducted with a total of 15 teachers including 5 elementary teachers, 5 visual arts teachers, 5 music teachers, who work in seven different schools, three of whom work in primary and four in middle schools. The data was collected by a semi structured interview form designed by the researchers. The data were analyzed by using the content and descriptive analyses. As a result of the research, regarding the use of creative drama in teachers' art education courses; it was found that they used creative drama mostly in music courses, besides they used creative drama method in art course. They indicated that from a teacher’s perspective it engages students in the course more easily, from a student’s perspective it provides more active engagement, students can more easily express themselves regarding the space, and it makes the subject more understandable and thus permanent learning regarding the subject. Based on the results, there is a tight and bidirectional relationship between art and creative drama. In order to use creative drama more effectively, organizing in-service training courses where teachers can improve themselves, increasing the time allocated to art classes, creating drama workshops and providing material support are among the implications of this study.